Network meta-analysis of empirically derived component classes in parenting interventions for child conduct disorder - Melendez-Torres, G; Leijten, P; Knerr, W; Gardner, F (BMJ Publishing Group, 2017)
Child conduct disorders have important long-term public health sequelae, including higher risk of substance use and violence in adolescence and higher risk of mental health problems in adulthood. Parenting interventions informed by social learning theory have been consistently shown to be effective for reducing child disruptive behaviour, but the diversity and variety of interventions prevents a clear understanding of why interventions are differentially effective. Intervention components rarely exist in isolation, and interventions may be best understood in terms of the combinations of components they include rather than any one component. We tested if components of social learning theory-based parenting interventions for child disruptive behaviour outcomes formed underlying groupings across trials, and analysed how these groupings were associated with differential intervention effectiveness.